2017
DOI: 10.1177/0047287517721369
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Memorable Tourism Experiences on Loyalty Behaviors: The Mediating Effects of Destination Image and Satisfaction

Abstract: The current study develops a theoretical model of the effect of memorable tourism experiences (MTEs) on behavioral intentions by examining the structural relationships between destination image (DI), tourist satisfaction, revisit intention, and word-of-mouth (WOM) publicity. The results show that MTEs influence future behavioral intentions both directly and indirectly through DI and tourist satisfaction. Moreover, MTEs are found to be the most influential determinant of behavioral intentions. Thus, the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
492
7
58

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(593 citation statements)
references
References 111 publications
36
492
7
58
Order By: Relevance
“…Experiences are an area of strong academic and practical interest (Kim, 2010;Tung and Ritchie, 2011a;Volo, 2013;Kirillova et al, 2017). Tourists' seek memorable tourism experiences (MTEs) (Scott et al, 2017), which have the propensity to generate destination loyalty (Chen and Rahman, 2018;Zhang H. et al, 2018), increase satisfaction (Kim, 2018) and promote emotional engagement (Michalkó et al, 2015). However, the creation of memorable experiences requires an understanding of the mental processes which occur at different stages of a tourist experience, including the antecedent and consequent conditions (Knobloch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiences are an area of strong academic and practical interest (Kim, 2010;Tung and Ritchie, 2011a;Volo, 2013;Kirillova et al, 2017). Tourists' seek memorable tourism experiences (MTEs) (Scott et al, 2017), which have the propensity to generate destination loyalty (Chen and Rahman, 2018;Zhang H. et al, 2018), increase satisfaction (Kim, 2018) and promote emotional engagement (Michalkó et al, 2015). However, the creation of memorable experiences requires an understanding of the mental processes which occur at different stages of a tourist experience, including the antecedent and consequent conditions (Knobloch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of MTEs have focused on concepts such as motivation (Gnoth and Matteucci, 2014;Prayag et al, 2017;Yoo et al, 2018;Passafaro, 2019), expectations and satisfaction (Tynan and McKechnie, 2009;Kim, 2018), well-being and quality of life (Uysal et al, 2012), as well as emotions and memories (Chandralal and Valenzuela, 2015;Moyle et al, 2019). Psychological antecedents of MTEs include hedonism, involvement, knowledge, refreshment, meaningfulness, and novelty (Chandralal and Valenzuela, 2013;Kim, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given the relatively nascent state of research, there is limited empirical work directly related to how the country of origin affects rating behavior. Furthering this path has led to some recent studies (Kim 2018;Gao et al 2018) who look at the country of origin effects relating to online review ratings and culture and its effects relating to online review ratings respectively. Less well examined too, is the role of language in online hotel ratings (Schuckert, Liu, and Law 2015;Yong et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Weaver et al [101] point out in their study that part of the variation in the assessment of the destination and in the intention to return can be attributed to previous travel experience and the characteristics of the holiday. Authors such as Woodside, Caldwell and Albers-Miller [22], Kim and Ritchie [71] and Kim [105] report similar findings: the intention to return to a destination, the intention to recommend and the generation of positive word-of-mouth recommendations are the result of previous positive experiences of tourists. Also, Marschall [106], in his work on the role of memory in tourism, points out that tourists like to return to destinations that they have fond memories of.…”
Section: Memorable Experiences Loyalty and Intention To Recommendmentioning
confidence: 74%
“…For this author, memory is a crucial factor in the choice of a destination; it is based on the tourist's experience in the destination and on sharing the experience with others after the trip, in particular, through sharing texts, memories, stories, photos and souvenirs. Tsai [107] and Kim [105], for example, from a sample of Taiwanese tourists, demonstrated the predictive validity of memorable tourist experiences (MTEs) on the future behaviour of returning to a tourist destination, as they found that five of the seven components on their MTE measurement scale (i.e., hedonism, involvement, local culture, meaningfulness, and refreshment) influenced behavioural intentions to return to the destination, participate in the same tourism programmes and promote word-of-mouth recommendations. Tsai [107], in his study of a sample of tourists who visited Tainan in Taiwan, for example, considered the value of culinary experiences as a fundamental factor in generating positive and unforgettable memories that affect future behavioural intentions to return to the destination.…”
Section: Memorable Experiences Loyalty and Intention To Recommendmentioning
confidence: 99%